Object-based inhibitory priming in preview search: evidence from the "top-up" procedure. - Kunar, M; Humphreys, G (2006)
Visual search in a conjunction task can be facilitated if half the distractor items are previewed prior to the other half of the distractors and the target item. Here, we investigate the nature of this preview by using a top-up procedure, which presents an initial preview followed by a secondary preview after a period of time (the offset period). In Experiment 1, we demonstrate that increasing the time of the offset period decreases search efficiency. If the offset period is increased to 2 sec, the previewed items are searched to a greater extent than when the offset period is 450 msec. This holds even when the old items remain in the same positions across presentations and when they differ in color from new search stimuli. However, when the offset intervals are reduced, the preview can be discounted from search even when the old items change locations between exposures (Experiment 2) and when they are not distinguished from search displays by their color (Experiment 3). The last result occurs only as long as the preview items can be grouped in terms of form. When the preview stimuli are heterogeneous, they are no longer discounted from search if their locations change across the offset period (Experiment 4). We interpret the data in terms of object-based priming, which enables the repeated form of the old distractors to be filtered more easily from search.